HUBUNGAN TINGKAT KEBUGARAN JASMANI DENGAN KAPASITAS VITAL PARU-PARU MAHASISWA PRODI SARJANA KEPERAWATAN UNIVERSITAS KUSUMA HUSADA SURAKARTA - gatot suparmanto suparmanto; Ika Subekti Wulandari; Sahuri Teguh Kurniawan (Viva Medika, 2021)
Daily activities require physical fitness so that the body can keep up with activities, as well as activities in student lectures are required to be able to attend lectures well and be supported by the vital capacity of the lungs to get maximum oxygen when inspiration and expiration and delivered throughout the body and this becomes a good indicator of lung function. The purpose of this study was to link the fitness level with the vital capacity of lungs in college students. This research method is descriptive correlative, which examines the relationship between variables using a cross-sectional approach. Data collection was carried out in the period September-October 2019, the subjects of this study were 52 final level undergraduate study program students. Examination of vital lung capacity will be measured by spirometry and fitness level is measured by Harvard step-up bench. Results: The mean value of the impurity level was 72 ± 8.84, while the mean value of vital lung capacity in this study was 3.528 ± 0.820 liters. The Spearman test was used to determine the relationship between the level of fitness and the vital capacity of the lungs, the p value was 0.000 (p <0.05) that there was a relationship between the vital capacity of the lungs and the fitness level he Spearman correlation of 0.605 indicates a positive relationship, or in other words, strong strength. Conclusion: There is a strong relationship between fitness level and lung vital capacity. The higher the fitness level of the vital lung capacity